PENGELOLAAN BARANG INVENTARIS PADA KANTOR KOMISI PEMILIHAN UMUM KABUPTEN BUTON - Sartono Sartono; Nofita Satia (Universitas Halu Oleo, 2021)
The purpose of this study is to determine the management of inventory good and to know the influencing factors of inventory goods management at the general election commission office of Buton regency. Data collection technique using observation techniques, interviews, and documentation. The data analysis technique in this research is using qualitative descriptive analysis techniques. Informants in the study amounted to 5 (five) people at the general election commission office of Buton regency. The results of this study indicate that the management of goods in the general election commission office of Buton regency is less that optimal, it can be seen that there is no special warehouse for goods, and more attention to goods so as not to be damaged, while the factors in the office are slightly improved with regard to inventory goods, there is always recording of goods and making reports by employees, regarding asset reporting techniques, it is further improved and it is necessary to check goods every month so that they can be known about goods that are suitable for use or not, then there is no such thing as Bimtek an the general election commission office Buton regency.